Subverting the Prince Charming Trope: Female Empowerment in the Disney Frozen Series - Hung-Chang Liao; Yu-Heng Lee; Ya-Huei Wang (k@ta: A Biannual Publication on the Study of Language and Literature, 2026)
This research explores how contemporary feminist reinterpretations of classic fairy tales subvert traditional gender stereotypes. It focuses specifically on the “Prince Charming” and “waiting-for-rescue” narratives to represent female empowerment and autonomy. Using Disney’s animated films Frozen and Frozen II as case studies, the study employs qualitative content analysis integrated with feminist visual text analysis, informed by feminist theory, postfeminist media culture, gender performativity theory, and contemporary feminist media studies. Through the analysis of selected scenes, dialogue, song lyrics, and visual elements, the research examines the transformation of women’s passive roles within 21st-century feminist discourses shaped by neoliberal individualism and fourth-wave critiques of representation. Special attention is given to the character development and identity formation of the heroines, Elsa and Anna, to show how the films retell classic fairy tale themes through a feminist lens. The findings show that Frozen and Frozen II challenge entrenched gender norms, foreground female agency, and offer a contemporary framework for understanding women’s empowerment and self-determined autonomy in popular media.